ANALISIS USAHATANI GAMBIR DI SUMATERA BARAT (STUDI KASUS KECAMATAN HARAU, KABUPATEN 50 KOTA) - ERMIATI A. F.; PUTI ROSMEILISA (Jurnal Penelitian Tanaman Industri, 2001)
Analysis of gambir farming system (Uncaria gambir Roxb) in West Sumatra (case study of Harau Sub District, 50 Kota District)Prospect of gambir cither for domestic or export markets is very potential. However, this prospective cash crop, is not immediately followed by the improvement of its productivity and farmers income. This condition, may due to the fact thai until now farmers have used Ihe recommended technology for cultivation and processing and the farmers, have limited capital for developing gambirs farming system. The objective of this research was to study the feasibility and contribution of gambir farming system (o the farmer prosperity, and the constraint of developing gambirs farming system in this region. The research was conducted al Kelinggian villages, Harau f>ub District. 50 Kola District. West Sumatra in November 1999 using survey method. Thirty respondents were taken by simple random farmers income was analyzed through income analyses. While the feasibility of farming system was analyzed through Beneit Cost Ratio, Net Pesent Value (NPV), and Internal Rale of Retun (IRR). The results of feasibility analysis, based on discount factor of 15%. showed thai a gambir farming system at len years old had that B/C Ratio 1.22, NPV Rp. 3 657 433, and IRR 43% At discount factor of 18%. B/C ratio was 1.20, NPV was Rp 2 890 075, and IRR 43%. The share of gambir farming system to farmers income was Rp. 1 1 548 750 or Rp. I 154 875 per hectare per year Based on Ibis study, it was concluded that gambir farming system in Kelinggian Village. Harau Sub Distict, 50 Kota Dislriel was proitable and feasible lo be developed. Recently, the limited capital. becomes a problem for developing gambir farming. This resulted the farmers unable to adopt the technology for cultivation and processing. More over, the bargaining position of farmers is also weak, due to buycr- up system. It is, therefore, suggested that the Village Cooperative Unit (KUD) is supported, in order to supply the production inputs and the product.